Nurses’ Compliance with the Catheter Associated Urinary Tract Infection Prevention Bundle - Latief, Nur Annisha Karunia; Kurniawati, Ninuk Dian; Pratiwi, Ika Nur (International Journal of Psychosocial Rehabilitation, 2020)
Catheter-associated Urinary Tract Infection (CAUTI) was the fourth most common infection and results in increased morbidity, mortality, maintenance costs and length of stay. Prevention and Control of CAUTI were carried out by nurses through bundles. This study aimed to analyze the determinants of nurses' compliance behavior in the implementation of the CAUTI bundle with the Theory of Planned Behavior (TPB) approach. The study design was cross sectional study. A total of 111 nurses recruits with simple random sampling participated as the sample. Compliance with the implementation of the CAUTI bundle was the dependent variable whereas the independent variables were background factors, attitudes, subjective norms and intentions. The instrument used consisted of questionnaires. A logistic regression test (0.05) was used to determine the determinants of nurse compliance behavior. Educational background factors (p=0.039) and knowledge (p=0.014) was related to attitudes, knowledge (p=0.023) and work experience (p=0.020) related to subjective norms, attitudes (p=0.008) and subjective norms (p = 0.003) related to intention, and intention related to behavior (p=0.000) and had a value of r = 0.510 which means that the relationship between intention and behavior was quite strong. In conclusion, a factor that was directly related to the compliance in the implementation of the CAUTI bundle was the nurse’s intention and the factors that were indirectly related were attitudes, subjective norms, and background factors (knowledge, education and length of work).